Penyuluhan Kesehatan Tentang Prosedur Evakuasi Saat Terjadinya Gempa Bumi Di Desa Wonorejo Karanganyar - Gatot Suparmanto; Ika Subekti Wulandari (Universitas Medan Area, 2021)
Earthquakes in Indonesia cause physical damage as well as fatalities, high mortality rates and disability when an earthquake occurs, it is necessary to reduce or prevent it by increasing people's knowledge and skills about how to evacuate during an earthquake. Earthquakes that are not resolved with resilience and lack of human resources that can handle earthquakes from pre-disaster, during disaster and post-disaster. Earthquakes are caused by the movement of the Earth's crust (Earth's plates). The frequency of a region, refers to the type and size of earthquakes experienced over a period of time. Earthquakes are measured using a seismometer. Moment magnitude is the most common scale where earthquakes occur throughout the world so that the community is demanded to be prepared, one of which is evacuation during a disaster which is held by evacuation counseling in Wonorejo Village, Karanganyar. earthquake with pre-test data 75% of the residents did not know and after counseling and post-testing it was found that 90% of the residents understood the skills and knowledge of evacuation during an earthquake. with the lack of knowledge and skills of residents regarding evacuation during an earthquake, it is very appropriate for residents to understand when an earthquake occurs